Flexible highly conductive films based on expanded graphite /polymer nanocomposites - Nista, Silvia V. G.; Alaferdov, Andrei V.; Isayama, Yuri H.; Mei, Lucia H. I.; Moshkalev, Stanislav A. (Frontiers in Nanotechnology, 2023)
Highly electrically and thermally conducting films of expanded graphite/polymer nanocomposites were fabricated using an approach based on solution mixing methods. The use of Hydroxyethylcellulose and benzylic alcohol based solutions provides efficient dispersion and better exfoliation of multilayer graphene (nanographite) flakes that are further aligned in extended 2D layers forming continuous conductive pathways during lamination (hot calendering) process. Very high electrical conductivity (190 S/cm) was obtained for fabricated layered films. In contrast, for films produced by a conventional mixing and deposition method with acrylic copolymer and the same nanographitic material, with flakes randomly distributed within the composite, much lower conductivities (2.4 S/cm) were obtained.